Loss of HtrA2/Omi activity in non-neuronal tissues of adult mice causes premature aging - Kang, S (Nature Publishing Group, 2013)
mnd2 mice die prematurely as a result of neurodegeneration 30–40 days after birth due to loss of the enzymatic activity of the mitochondrial quality control protease HtrA2/Omi. Here, we show that transgenic expression of human HtrA2/Omi in the central nervous system of mnd2 mice rescues them from neurodegeneration and prevents their premature death. Interestingly, adult transgenic mnd2 mice develop accelerated aging phenotypes, such as premature weight loss, hair loss, reduced fertility, curvature of the spine, heart enlargement, increased autophagy, and death by 12–17 months of age. These mice also have elevated levels of clonally expanded mitochondrial DNA (mtDNA) deletions in their tissues. Our results provide direct genetic evidence linking mitochondrial protein quality control to mtDNA deletions and aging in mammals.